THEORY ELEMENTS OF ZERO NEGATIVE-FEEDBACK IN ADAPTIVE FRICTION CLUTCHES - Mikhail Pavlovich Shishkarev; Kirill Olegovich Kobzev (Advanced Engineering Research, 2014)
A supplementary friction group in the clutch design increases its load capacity. It is a decided adv antage of adaptive friction clutches of the second generation with combine d feedback. The feedback gain changes depending on the friction coefficient value. The problem of establishing such patterns, and the synthesis of the comm and unit el eme n tary diagram with its parametrization based on this concept, is solved in the paper. T he identified regularity allows stating the following. Under zero thrust force and minimum friction coefficient value, changi ng the gain level does not exceed its limit value. It provides an automatic control with a theoretical “ideal” load ch aracteristic of the clutch. A curve geometric form outlining the side wall of the rolling body socket of the command uni t, and providing an automatic control in the adaptive friction clutch, is found. In this case, the goal is to obtain a theoretically “ ideal ” load cha racteristic of the coupling.